2015
DOI: 10.1111/apce.12085
|View full text |Cite|
|
Sign up to set email alerts
|

Are Financial and Social Efficiency Mutually Exclusive? A Case Study of Vietnamese Microfinance Institutions

Abstract: A major debate in microfinance focuses on the existence of a trade-off between the financial sustainability of microfinance institutions (MFIs) and their outreach to poor clients. This paper adds to this debate by analyzing whether financial and social efficiency are mutually exclusive in a context of implicit subsidies by the state and international donors. We use data from a sample of 28 Vietnamese MFIs and apply Data Envelopment Analysis (DEA) to identify the existence of a trade-off. Our analysis shows tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 46 publications
(53 reference statements)
6
76
0
5
Order By: Relevance
“…Lebovics et al . () conclude that subsidies allow Vietnamese MFIs increasing their social efficiency. Forcella and Hudon () find that MFIs with better environmental performance also benefit from more donor interest.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Lebovics et al . () conclude that subsidies allow Vietnamese MFIs increasing their social efficiency. Forcella and Hudon () find that MFIs with better environmental performance also benefit from more donor interest.…”
Section: Discussionmentioning
confidence: 97%
“…Lebovics et al . () explain that subsidies help MFIs to achieve high financial efficiency in Vietnam. This result is corroborated in a study by Tahir and Che Tarim () on the efficiency of Vietnamese MFIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty‐nine per cent of the MFIs were NPOs, illustrating the important influence of nonprofit firms in the microfinance industry (Lebovics et al. ). At the same time, 41 per cent were FPOs, which provided a relatively well‐balanced setting for testing the differences between NPOs and FPOs.…”
Section: Data and Summary Statisticsmentioning
confidence: 99%
“…The main source of inefficiency, including overall, financial and social, is technical inefficiency. When it comes to the question of whether financial and social efficiency are mutually exclusive, Lebovics et al (2016) found in 28 Vietnamese MFIs for the year 2011 that there was no correlation between those two types of efficiencies, meaning that there is no tradeoff between them. They stress that where financial efficiency is concerned, learning effects and cost-efficiency seem to be crucial, whereas for social efficiency the quality of staff and the quality of leadership of the top managers appears to be of the most importance.…”
Section: The "Two Dimensional" Efficiency Of Microfinance Institutionsmentioning
confidence: 99%